Congruence across taxa and spatial scales: Are we asking too much of species data?. Issue 8 (24th August 2018) - Burrascano, S.; de Andrade, R. B.; Paillet, Y.; Ódor, P.; Antonini, G.; Bouget, C.; Campagnaro, T.; Gosselin, F.; Janssen, P.; Persiani, A. M.; Nascimbene, J.; Sabatini, F. M.; et al.
Abstract: Aim: Biodiversity monitoring and conservation are extremely complex, and surrogate taxa may represent proxies to test methods and solutions. However, cross‐taxon correlations in species diversity (i.e., cross‐taxon congruence) may vary widely with spatial scale. Our goal is to assess how cross‐taxon congruence varies with spatial scale in European temperate forests. We expect that congruence in species diversity increases when shifting from fine to coarse spatial scales, with differences between species richness and composition, and across pairs of taxonomic groups. Location: European temperate forests. Time period: Present. Major taxa studied: Vascular plants, bryophytes, birds, epiphytic lichens, saproxylic beetles and wood‐inhabiting fungi. Methods: We used field data (354 plots across 23 sites) encompassing Italy, France and Hungary, with species information for six taxonomic groups. We accounted separately for spatial grain (the size of elementary sampling unit) and extent (the geographical area included in the survey) and evaluated the relationships within all the possible pairs of taxa. Results: Although no pair of taxa had its species richness consistently correlated across scales, we found no changes in the direction of correlations when analysing species composition. However, when increasing grain and extent, we did find a general increase in the magnitude of correlations in species composition and partial changes in significance, with plants having the highest number of significant correlations. Main conclusions: Species richness congruence among taxa is strongly scale dependent owing to differences in the relative contribution of large‐ and small‐scale processes across taxa. Cross‐taxon congruence in species composition is scale dependent only for its magnitude, because life‐history traits of individual species make responses to environmental factors similar across scales. Forest monitoring should consider multi‐taxon sampling and limit the use of surrogates at specific spatial scales, especially for species richness. Sampling plant species composition in scattered plots across different sites may effectively summarize the whole community composition.